PARTISIPASI PARALEGAL DALAM PENDAMPINGAN HUKUM NON LITIGASI BAGI TENAGA KERJA INDONESIA LUAR NEGERI (STUDI PADA FORUM WARGA BURUH MIGRAN NUSAWUNGU KABUPATEN CILACAP) - Robiat Tri Cahyani; Machmud Al Rasyid; Triana Rejekiningsih (Asosiasi PPKn, 2019)
The purpose of this study was to find out: (1) Participation of the Paralegal Forum of the Nusawungu Migrant Workers' Forum in non-litigation legal assistance for overseas migrant workers, (2) Impact of TKI from non-litigation legal assistance carried out by the paralegal Forum of Nusawungu Migrant Workers, (3) Constraints on the Paralegal Forum of Nusawungu Migrant Workers in non-litigation legal assistance to TKI. This study uses descriptive qualitative research methods. Data sources were obtained from sources, places and events, and documentation. The sampling technique uses purposive sampling. The technique of collecting data is by interviewing, observing, and analyzing documents. Data validity using data triangulation and triangulation method. While data analysis techniques use an interactive analysis model with stages: (1) data reduction, (2) data presentation, (3) drawing conclusions. The research procedures with steps as follows: Selection of the topic of study, Instrumentation, Management of research, Data Processing, Research Results. Based on the results of this study, it can be concluded that (1) Paralegal Participation Forum of the Nusawungu Migrant Workers in non-litigation legal assistance for Indonesian migrant workers has been good, because it has been able and tried to resolve cases and it is proven that some cases have been fulfilled but needs to be improved again because there are cases that cannot be resolved. Paralegal participation is shown by several activities in assisting TKI cases to be resolved in non-litigation, namely providing information, receiving complaints cases, collecting data,collecting evidence, making complaints, mediation and negotiations. (2) Paralegal participation in legal assistance has the following impacts: cases completed, TKI rights fulfilled, reduced number of cases, reduced costs, getting information related to working abroad and how to resolve cases,and TKI get access to justice. (3) Participation of Forum Paralegal Nusawungu Migrant Workers in non-litigation legal assistance for Indonesian migrant workers is influenced by several constraints, namely limited funds, the number of paralegals, complainants or migrant workers and defendants are difficult to work with.   Full Paper